Peningkatan literasi digital (Pelita) layanan kesehatan inklusif untuk komunitas transgender di Palembang - Rizma Adlia Syakurah; Muhamad Ridwan Afandi; Fitri Aulia; Putri Inrian Tari; Muhammad Naufan Rizqullah (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2026)
Enhancing Digital Literacy (PELITA) for Inclusive Health Care Services among Transgender Communities in Palembang. This community engagement program addresses the digital literacy gap that hinders transgender communities in Palembang from accessing inclusive digital health services. Despite Indonesia’s rapid digital health transformation. through platforms such as Mobile JKN, SATUSEHAT, Halodoc, and Alodokter. Many transgender individuals encounter layered barriers including limited technical skills, low confidence, and history of discrimination in health facilities. The PELITA program was designed to enhance their e-health literacy through a participatory and community-based approach. Activities included needs assessment, conceptual training on digital health literacy and data security, hands-on practice using major digital health applications, and individualized assistance through the Klinik Digital Mandiri. Data were collected using pre-test, post-test, observation sheets, and brief interviews. Quantitative analysis using descriptive statistics and the Wilcoxon test showed a significant improvement in participants’ knowledge, with increases in correct responses and enhanced ability to navigate health applications. Qualitative findings indicated notable progress in participants’ competence in creating and managing email accounts, accessing digital queues, retrieving electronic medical records, conducting teleconsultations, and evaluating the credibility of online health information. The program also strengthened psychological readiness and confidence in interacting with digital health services. To ensure sustainability, Digital Literacy Ambassadors were appointed from among participants who demonstrated strong competence and motivation. Overall, the PELITA program successfully improved transgender community members’ capacity to access and utilize digital health services independently and safely, while fostering an inclusive health ecosystem that supports their rights and reduces inequalities in digital health access